PENGARUH BELANJA PUBLIK DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI KALIMANTAN BARAT - Yacoub, Yarlina; Adelia, Resty (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2011)
Public finance and economic growth can be regarded as important intruments in reducing poverty in most developing countries. The objectives of this study in to sheds light on the impact of public finance and economic growth on the poverty level in West Kalimantan for the period 2004-2008. This study uses descriptive-associative method. By using regression model, the results show that partially either public finance or economic growth influences positively and significantly on poverty level. Simultneously, both variables have an impact siginifivicantly on the poverty level in West Kalimantan.